(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper aims to examine how Wu Tiecheng (1888–1953), one of the Kuomintang (KMT) and Republican China senior statesmen, had established and developed his three crucial assets: guanxi ( ?? relationships or connections), networks and eloquence since his formative years (1888–1910) until the 1911 Revolution in Jiujiang, China. His uniqueness as a revolutionary who was equipped with those three elements nurtured during the formative years of his youth was subsequently reflected during the revolution. Concurrently, this will explore prior and during the revolution, what types of guanxi and networks he had tried to establish, subsequently develop and even utilise. Furthermore, this paper also attempts to look into how those guanxi, networks and even eloquence had assisted Wu in his endeavours to become one of the leading revolutionaries in this revolution. In probing into the above mentioned aspects, it would trace the activities he had involved and roles played. Three essential elements apart from moulding and influencing Wu, had become part of his social capital which benefitted him and continuously to be utilised in the coming years. Those had given impetus to his rise within the KMT and Republican political circles, and also made him a distinct figure among peers.